PERANAN SEKTOR PERKEBUNAN TERHADAP PEREKONOMIAN PROVINSI RIAU: ANALISIS STRUKTUR INPUT-OUTPUT - Hasanah, Huswatun; Bakce, Djaimi; Dewi, Novia (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Plantation sector has an important role for the economy of Riau Province, among others, as a provider of employment and sources of income for farmers, the sources of industrial raw materials and sources of basic necessities as well as foreign countries. The purpose of this research is to analyze the role of the plantation sector to the economy of Riau Province through a review of the structure of input-output. The data used in this research is a data input-output table of Riau Province based on producer price transactions in 2012 with the classification of the 17x17 sector of the regional development planning Board (Bappeda) of Riau Province. Results of the analysis show that: first, the plantation sector contributes to the economy of Riau Province. Three plantation sectors, which have high contribution is the sector of palm oil, rubber and coconut sector. Second, in terms of output, component output forming plantation sector more driven by intermediate output followed by investment and consumption. Thirdly, the establishment of the component input, the more the economy is driven by the producer surplus, followed by intermediate input and wages/salaries. Based on those results, in order to encourage economic growth through the development of the plantation sector needs the efforts of the Government and the private sector to increase investment, especially the accumulation of capital sourced from producer surplus. Keywords: the role of the plantation sector, input-output table, producer surplus Â